HUBUNGAN KONSUMSI SUGAR-SWEETENED BEVERAGES DENGAN KEJADIAN DIABETES MELLITUS PADA LANSIA[The Correlation Between Sugar-Sweetened Beverages Consumption and Diabetes Mellitus in Elderly] - Putri Ramadhani; Trias Mahmudiono (Media Gizi Indonesia, 2018)
Elderly becomes the most risky group in developing type 2 diabetes because they are more susceptible for carbohydrate metabolism disorders that can appear as diabetes. This study was aimed to determine the correlation between consumption of sugar-sweetened beverages and sex with the incidence of diabetes mellitus in the elderly. The population in this study were all elderly population (age> 60 years) in Jagir Public Health Center working area. This research used case control design with simple random sampling technique as a sampling method. The number of samples was 78 respondents with 39 samples of case group and 39 samples of control group. Data were analyzed using linear regression and logistic regression test. The results showed that there was a correlation between the consumption of SSBs and the incidence of diabetes mellitus in elderly (p = 0.000; OR = 9.375). Female elderly consumed more SSBs than men elderly (female's sugar consumption 26.9%, brown sugar 69.2%, syrup 75.6% and sachet drinks 73.1%, while mal’s sugar consumption 9%, brown sugar 20.5%, syrup 16.7% and sachet drinks 15.4%). In conclusion, this research revealed consumption of SSB’s was higher in female elderly and SSB’s consumption was correlated with the incidence of type 2 diabetes mellitus.